Інноваційний маркетинг в системі стратегічного управління розвитком організацій сфери послуг - Ілляшенко, Сергій Миколайович; Ронь, Ярослав Олексійович (Видавничий дім "Гельветика", 2025)
Статтю присвячено розробленню підходу до управління інноваційним розвитком організацій сфери послуг на засадах інноваційного маркетингу. Дістало подальшого розвитку поняття інноваційного маркетингу, зокрема, з позицій урахування впливу технологічних трансформа цій четвертої промислової революції на інноваційний розвиток організацій і роль маркетингу в ньому. Запропоновано варіант структури інноваційного маркетингу, в якому поєднано його цілі, завдання, інструментальне забезпечення. Розроблено концептуальну схему управління інноваційним розвитком організації сфери послуг на засадах інноваційного маркетингу, окрес лено комплекс його основних завдань. Отримані результати розвивають методологічні засади управління розвитком організацій сфери послуг в руслі концепції інноваційного маркетингу, яка передбачає поєднання інноваційного і маркетингового управлінських підходів, що сприяє стійкому інноваційному зростанню сфери послуг в перманентно мінливих умовах сучасної економіки.

The article is devoted to developing an approach to managing the innovative development of service organizations based on innovative marketing. The concept of innovative marketing has been further developed, in particular, from the standpoint of considering the impact of technological transformations of the fourth industrial revolution on the innovative development of organizations and the role of marketing in it. Innovative marketing is viewed as a concept of running innovative business focused on the search for new areas and ways of realizing the potential of the organization, which is associated with radical transformations of existing markets and the formation of new ones. It involves creation of innovative products and the use of improved or fundamentally new marketing tools, forms and methods in order to solve problems and meet consumers’, producers’ and other market entities’ demands, as well as to ensure conditions for sustainable innovative growth. A version of innovative marketing structure is proposed, combining its goals (strategic and operational), tasks for their achievement (strategic analysis and marketing support of innovative products and services on the market), and the necessary instrumental support. A conceptual scheme for managing the innovative development of a service industry based on innovative marketing has been developed, a set of its main tasks has been outlined, the sequence and content of the procedures for their solution have been identified. It is proposed to determine the type of direction of innovative development by the degree of its radicalization in relation to the market leader (catching up, following the leader, overtaking) taking into account the level of innovative culture of the service provider and their target consumers (actual or prospective). Regarding the innovative culture of market entities allows to improve the quality of substantiation of strategies for innovative development of service industry organizations. The results obtained develop the methodological principles of managing the development of service organizations in line with innovative marketing, which involves a combination of innovative and marketing management approaches, contributing to the sustainable innovative growth of the service sector in the constantly changing conditions of the modern economy.
Innovative marketing in the system of strategic management of the development of service organizations
Keywords: інноваційний маркетинг; сфера послуг; управління розвитком; інноваційний розвиток; організації сфери послуг; innovative marketing; service sector; development management; innovative development; service organizations